Survey Of Student Interest In Participating Pencak Silat Extracurricularies At SMP Negeri 30 Muaro Jambi - Junianto, Toto; Indrayana, Boy; Yusradinafi, Yusradinafi (Athena: Physical Education and Sports Journal, 2024)
Abstract: This research was conducted at SMP Negeri 30 Muaro Jambi in May 2024. Research data was obtained by distributing questionnaires to students as the main data. After the questionnaire was returned, the data was analyzed quantitatively using a percentage formula. The results of the research show that the results of the analysis that have been carried out show that students' interest in participating in the pencak silat extracurricular at SMP Negeri 30 Muaro Jambi is known to be in the "very low" category at 3.3% (4 students), "low" at 31.3% (37 students), “medium” at 37.9% (45 students), “high” at 20.0% (24 students) and “very high” at 7.5% (9 students). The causal factors are internal factors and external factors. Internal factors come from indicators of happiness, attention and activity, where the percentage level shows that students' interest in participating in the pencak silat extracurricular at SMP Negeri 30 Muaro Jambi based on internal factors in the happiness indicator is 35.61%, the attention indicator is 32.03% and the activity indicator was 32.37%. External factors come from environmental indicators and parents, where the percentage level shows that students' interest in participating in pencak silat extracurriculars at SMP Negeri 30 Muaro Jambi is based on external factors in environmental indicators of 49.48% and parental indicators of 50.52%.